Concentration, distribution, and correlation of heavy metals in seawater, sediment,and Cerithidea obtusa from coastal waters of Singkep Island, Riau Archipelago Province - Amin, Biotal; Nurrachmi, Irvina; ', Jamalus (Universitas Riau, 2014)
Concentration, distribution and correlation of seven heavy metals in seawater, sediment and gastropod Cerithidea obtusa from coastal waters in the proximity of abandoned tin mining in Singkep Island has been evaluated. Samples were taken from five stations and heavy metal analysis was carried out by using AAS Perkin Elmer 3110 in Marine Chemistry Laboratory Faculty of Fisheries and Marine Science University ofRiau. The mean concentrations ofCd, Cu, Pb, Zn, Ni, Mn and Cr were 0.0373, 0.0776, 0.1340, 0.1692,01789, 0,1205 and 0.3232 mg/1 in seawater; 2.0445, 11.5359, 24.6859, 23.7992, 13.2925, 13.1097 and79.0821 f.lg/g in sediment and 3.03, 69.71, 14.30, 120.73, 11.62, 56.29 and 18.75 J..lg/g in C. obtusa, respec tively. In general, the concentrations of metals in coastal water receiving effluents from abandoned tin mining activities in Singkep Island were higher than in coastal waters with less mining activities. Concentrations of all those metals in seawater were positively correlated with sediment and gastropod and its concentrations in sediment were also positively correlated with those in gastropod. Mean concentration of all metals in sediment were still below the ERM values, except for Cd which was exceeded the ERL but they were all still below the ERM values. Continuous environment monitoring programs should be implemented in Singkep Island coastal waters to evaluate possible increase of heavy metal threat as some new sand and bauxit mining activities are taking place.Key words: heavy metal, seawater, sediment, Cerithidea obtusa, mining